Teknik Penggunaan Teknologi Kecantikan Mesotherapy Acne Untuk Mengatasi Wajah Berjerawat - Nurulisma Saputri; Risma Putri Widya Sari; Agus Susanti (Garina, 2023)
Acne is a chronic disease caused by blockage of the oil glands in the skin. The beauty treatment for treating acne is Mesotherapy Acne, which is a treatment technique that incorporates certain substances into the subcutaneous fat tissue. The purpose of this study was to find out the treatment techniques and the effectiveness of Mesotherapy acne technology. The method used in this study is the method of R&D, interviews, observation, documentation and literature. This research developed three acne facial care techniques, namely the technique of pulling up, rotating, and pressing. The author made different studies based on duration, technique, procedure and type of treatment. Product validation of acne facial care technique books using acne mesotherapy beauty technology was carried out by 2 beauty lecturer validators. The results of the scores for all content aspects, display aspects, language aspects, and supporting questions obtained a total score of 28 and 29. Intervals 0-16 are not accepted and 17-32 are accepted. The conclusion of the validation results from the two validator data used is acceptable. Based on these three techniques, the upward pulling motion is effective because it can reduce acne. It is recommended that a guidebook for acne facial care techniques using mesotherapy acne beauty technology can be further investigated because it is effective in dealing with acne skin problems. Prepare a maintenance technique book that is copyrighted nationally so that it can be used as teaching material for beauty field reading books.